(untitled) (Ameghiniana, 2017)
A new genus and species of ornithomimosaur, Afromimus tenerensis, is described based on a partial skeleton from the Lower Cretaceous (Aptian-Albian) El Rhaz Formation of Niger. The holotype and only known individual preserves caudal vertebrae, chevrons and portions of the right hind limb. Derived ornithomimosaurian features include the broad, peanut-shaped articular surfaces of mid caudal centra, parasagittal fossae on mid caudal centra for reception of the postzygapophyses of the preceding vertebra, and a raised, subtriangular platform on the ventral aspect of the pedal phalanges. New information is given for, and comparisons made to, the basal southern African ornithomimosaur Nqwebasaurus thwazi. Ornithomimosaurs are unusual among coelurosaurian clades with major radiations on northern landmasses; the oldest undoubted member and now another basal form are known from a southerrn landmass, Africa.